Tinjauan Mohammad Arkoun tentang Bahasa Arab, Teks dan Semiotika Al-Qur'an - Ismail Suardi Wekke (AL-Fikr, 2013)
Deeply rooted traditions have accumulated the understanding of Islamic thought which, to some extent, brings about some misconduct in contemporary Islamic practices. To this regard, Arkoun, among other Muslim scholars, offers technical suggestions in reading the Qur’an.  This research explores Arkoun’s ideas related to the study of the Qur'an by looking at the aspect of Arabic as the language of the book with a semiotic perspective.   This article shows that Arkoun proposes a method of comprehending the value of the Qur’an through deconstruction techniques. Moreover, Arabic literature has solidly developed a biblical strength on the basis of the language itself, and this potential will be enhanced when combined with semiotics. Reading through the framework of the signified and signifiers in a semiotic study will encourage appreciation of text reading. In this light, Arkoun argues on the significance of assessment tools within the border of Islamic studies. Consequently, along the composition of his ideas, modern knowledge such as philosophy, anthropology, and other applied linguistics are implemented as an integrated part of Islamic studies. At the end, a comprehensive reinforcement of knowledge will open up the possibility to obtain a new horizon or a broad view in Islamic intellectuality.